PENGARUH LAMA WAKTU PENGGETARAN ULTRASONIC BATH TERHADAP SIFAT MEKANIK DAN MORFOLOGI PATAHAN BIOKOMPOSIT PATI TAPIOKA/SERAT RAMI (BOEHMERIA NIVEA) - Mochamad Asrofi; Hairul Abral; Anwar Kasim; Adjar Pratoto; Herwin Gevin; Melbi Mahardika (ROTOR, 2017)
This study reported about mechanical properties and fracture surface of ramie fiber reinforced tapioca starch based biocomposites. The amount of fibers in matrix was kept constant at 10% from dry weight starch basis. Fabrication of biocomposites was solution casting. The effect of vibration duration from ultrasonic bath was 0, 15, 30, and 45 min. This treatment was applied to biocomposites while gelatinized. Tensile test was carried out to determine the mechanical properties of biocomposites. Fracture surface of biocomposites after tensile test was observed by using scanning electron microscopy (SEM). The result shows that, tensile strength increased when vibration time was added. The maximum tensile strength was obtained at 45 min vibration time with 2,84 MPa. This phenomenon was supported by SEM observation which indicate compact structure. Keywords: Tapioca starch, ramie fiber, biocomposites, mechanical properties, SEM